English Teachers Strategy of Teaching Speaking During Covid-19 Pandemic Era at Senior High Schools in Bengkulu City: English - Muthia Hamidah Hamidah; Alamsyah HArahap; Ira Maisarah (Edu-Ling: Journal of English Education and Linguistics, 2023)
The objectives of this research is to investigate strategy used by teacher in teaching speaking at senior high schools in Bengkulu city during Covid-19 pandemic era. Teaching strategy is specific method to achieve the particular end. Kayi, Brown and Tornburry proposed several strategies that can used by teachers in teaching speaking, such as discussion, role play, simulation, information gap, brainstorming, and many others. The sample of this research are six English teachers from SMAN 2, SMAN 3 and SMAN 5. Mix method was used in this research. The data were gathered by using questionnaire, observation checklist and field-notes. The findings showed that first, six teachers used eight strategies out of twenty strategies in teaching speaking, these are: discussion, information gap, brainstorming, story-telling, using recording, using live listening, drilling, stories and jokes. Meanwhile there are three most strategies used by teachers in teaching speaking, these are: brainstorming (28,8%), using live listening (24%) and stories and jokes (14,4%). Second, in the implementation of brainstorming strategy, teachers gave several questions to check students’ basic knowledge about the teaching material which will be given for students. In the strategy of using live listening, teachers explained the teaching material, then teachers clarified students’ understanding about the material. Meanwhile in the stories and jokes strategy, teachers used this strategy in the middle of teaching and learning process. In conclusion, teacher used the strategies based on teaching material and condition of students in the classroom. However teacher should find the appropriate strategies to make students active in teaching and learning. Keywords: Teaching Strategy, Covid-19 Pandemic Era, Teaching Speaking